Concurrent new drug prescriptions and prognosis of early breast cancer: studies using the Danish Breast Cancer Group clinical database. (2nd January 2018) - Cronin-Fenton, Deirdre; Lash, Timothy L.; Ahern, Thomas P.; Damkier, Per; Christiansen, Peer; Ejlertsen, Bent; Sørensen, Henrik T.
Abstract: Background : Myriad reports suggest that frequently used prescription drugs alter the viability of breast cancer cells in pre-clinical studies. Routine use of these drugs, therefore, may impact breast cancer prognosis, and could have important implications for public health. Methods : The Danish Breast Cancer Group (DBCG) clinical database provides high-quality prospectively collected data on breast cancer diagnosis, treatment, and routine follow-up for breast cancer recurrence. Individual-level linkage of DBCG data to other population-based and medical registries in Denmark, including the Danish National Prescription Registry, has facilitated large population-based pharmacoepidemiology studies. A unique advantage of using DBCG data for such studies is the ability to investigate the association of drugs with breast cancer recurrence rather than breast cancer mortality – which may be misclassified – or all-cause mortality. Here we summarize findings from pharmacoepidemiological studies, based on DBCG data, on the association between routinely used prescription drugs and risk of breast cancer recurrence. Results : Our findings suggest that concurrent use of glucocorticoids, ACE inhibitors, aspirin, NSAIDs, selective COX-2 inhibitors, digoxin, and opioids has little impact on breast cancer recurrence. Similarly, patients who use SSRIs concurrently with tamoxifen treatment are not at increased risk of recurrence. In contrast, post-diagnostic use of simvastatin, a lipophilic statin, correlates with a decreased risk of breast cancer recurrence, providing a rationale for a prospective randomized clinical trial investigating simvastatin as an adjuvant therapy for breast cancer. Conclusion : As a whole, findings of pharmacoepidemiological studies based on DBCG data provide reassurance to physicians and healthcare personnel who provide supportive care during and after cancer (including prescriptions for comedications) and to breast cancer survivors for whom the risk of breast cancer recurrence is a major concern.